Erythropoietin supplementation induces dysbiosis of the gut microbiota and impacts mucosal immunity in a non-diseased mouse model - Sarrabayrouse, Guillaume; Joulain, Corentin; Bessoles, Stéphanie; Chiron, Andrada S.; Abina, Amine M.; Hacein-Bey-Abina, Salima (Frontiers in Immunology, 2025)
A number of drug treatments are known to alter the dialogue between the gut microbiota and the immune system components in the digestive mucosa. Alterations in intestinal homeostasis are now well known to affect peripheral immune responses and favor the occurrence of a number of pathologies such as allergies and cancers. Erythropoietin’s known pleiotropic effects might explain the adverse events sometimes observed in anemic patients treated by erythropoiesis-stimulating agents (ESA). However, the impact of this therapeutic cytokine on the homeostasis of the intestinal tract has not previously been investigated in detail. By studying a mouse model of erythropoietin (EPO) supplementation for 28 days, we observed EPO-induced dysbiosis of the fecal microbiota characterized by a greater bacterial load, lower bacterial diversity and taxonomic changes. With regard to the mucosal immune system, an analysis of leukocyte populations in the small intestine and colon treatment revealed low proportions of ileal CD4 lymphocyte subpopulations (Treg, Tr17 and Th17 cells), IgA-secreting plasma cells, and a major macrophage subpopulation, involved in the control of lymphocyte responses. Our results provide for the first time a descriptive analysis of intestinal EPO’s regulatory properties and raise questions about the involvement of EPO-induced alterations in the microbiota and the gut immune effectors in the control of intestinal and peripheral immune responses.